Not in-service railway arched bridges and their future = Nieużytkowane kolejowe mosty sklepione i ich przyszłość - Juszczyk, Artur; Dankowski, Marek; Wysokowski, Adam (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
At the turn of the 19th and 20th century, on the areas of nowadays northern and western Poland, the railway infrastructure was developing rapidly. In the late 80?s of the previous century many of the railway lines, together with the whole infrastructure including bridges, were being closed down. The example of such practices can be the brick bridge located near Nojewo, Voivodeship wielkopolskie. This article presents the technical parameters of these bridges and their damages as well as ideas for the future development of the railway facilities.
Keywords: most sklepiony; wiadukt; rewitalizacja mostów; bridge structure; viaduct; revitalisation of bridges